Remaking the news : essasys on the future of journalism scholarship in the digital age - Boczkowski, Pablo J.; Anderson, C.W. (Cambridge [etc.] MIT Press, 2017)
The use of digital technology has transformed the way news is produced, distributed, and received. Just as media organizations and journalists have realized that technology is a central and indispensable part of their enterprise, scholars of journalism have shifted their focus to the role of technology. In Remaking the News, leading scholars chart the future of studies on technology and journalism in the digital age. These ongoing changes in journalism invite scholars to rethink how they approach this dynamic field of inquiry.
Keywords: Periodismo electrónico; Comunicación en educación; Periodismo -- Innovaciones tecnológicas; Periodismo -- Estudio y enseñanza; Libros electrónicos